Identificação das atitudes dos pais e familiares frente ao uso da chupeta - Pereira, Eny Regina Bóia Neves [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
Due to an innate and natural reflex, most of the babies tend to have the strong necessity of sucking any and every object placed near their mouths. The pacifier, when rationally and temporally used, can provide for and supply this appeal. In these cases, this usage allows the perfect balance of the stomatognathic complex by effectively supporting the eruption and the position of the deciduous teeth, as well as the correct articulation of the words. The aim of this study is to present a piece of research fulfilled in tw0 day-cares in the cittes of bauru and piratininga – sp, involving children with minor social-cultural differences, in order to verify the opinion and attitude of parents in relation of the pacifier usage frequency, as well as the efects this habit may provoke. This research aroused a significant conclusion most parents tend to present a certain convenient accomodation regarding the pacifier usage, whereas others, nevertheless knowing the damagesits long-term use may provoke, are totally unaware of the severe alterations the pacifier may cause.

A maioria dos bebês tem necessidade de sugar qualquer objeto que é colocado dentro ou próximo à sua boca, devido a um reflexo inato, natural. O uso racional da chupeta supre essa necessidade natural quando utilizada por período adequado. Nestes casos, permite obter um equilíbrio muscular do complexo estomatognático, favorecendo efetivamente a erupção e o posicionamento dos dentes decíduos e a articulação correta das palavras. Este estudo têm por objetivo apresentar uma pesquisa realizada em duas Creches das cidades de Bauru-SP e Piratininga-SP, em crianças com pequena diferença do padrão sócioeconômico- cultural, para verificar a opinião e atitudes dos pais em relação a freqüência do uso da chupeta e aos efeitos provocados por esse hábito de sucção. Conclui-se que a maioria dos pais apresentam uma situação de comodismo frente ao uso da chupeta e que muitos possuem conhecimento sobre os danos da utilização prolongada, mas desconhecem as alterações causadas.
Keywords: Crianças - Hábito da chupeta; Crianças - Desenvolvimento